Platelet-derived growth factor BB is reduced in endometrial endothelial cells of women with abnormal uterine bleeding–endometrial disorder - Biswas Shivhare, Sourima; Lu, Qinsheng; Sun, Dingqian; Hou, Huomei; Bulmer, Judith N.; Innes, Barbara A.; Hapangama, Dharani K.; Lash, Gendie E. (Reproductive biomedicine online, 2022)
What is the expression pattern of platelet-derived growth factor BB (PDGF-BB), and its receptors, across the menstrual cycle in healthy control women and those with abnormal uterine bleeding–endometrial disorder (AUB-E)? Immunohistochemical staining for PDGF-BB, platelet-derived growth factor receptor alpha (PDGFRα) and platelet-derived growth factor beta (PDGFRβ) was performed in control and AUB-E endometrium from the proliferative, early, mid- and late secretory phases of the menstrual cycle (n = 5 each group). Control proliferative phase endometrium was cultured in PDGF-BB (0, 10 ng/ml) and vascular maturation assessed (n = 3). Endothelial cell to vascular smooth muscle cell (VSMC) association was assessed after treatment with PDGF-BB (0, 1, 10 ng/ml). Secretion of angiogenic growth factors by endothelial cells or VSMC was determined. Endothelial cell immunoreactivity for PDGF-BB was reduced in the mid and late secretory phases in AUB-E (P = 0.008). PDGFRα was also reduced in mid secretory phase endothelial cells, proliferative and early secretory phase glandular epithelium in AUB-E (P = 0.008). PDGFRβ expression was not altered. Treatment of proliferative phase endometrium with PDGF-BB (10 ng/ml) reduced the percentage of vessels expressing contractile VSMC markers. PDGF-BB had no effect on angiogenic growth factor secretion by endothelial cells or VSMC in vitro and did not affect their association in an in-vitro endothelial cell–VSMC association assay. Reduced endothelial cell expression of PDGF-BB in the AUB-E endometrium may contribute to the reduced vascular maturation previously observed in these women.